Pengaruh Orientasi Karyawan dan Pelatihan Terhadap Kinerja Karyawan di Rumah Sakit Ibu dan Anak Sentul Cikampek - Mardiyanto, Mardiyanto; Rosidawati, Imas; Handayani, Nining (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
The aim of this research is to determine the effect of new employee orientation and training on knowledge of hospital profiles and products, so that it can improve employee performance at RSIA Sentul Cikampek. The low level of public satisfaction with the service time provided is caused by the fact that employees generally have not received sufficient orientation and training related to their work so that the time required to carry out their duties is longer and this causes patient complaints related to service. This research was conducted in the RSIA Sentul Cikampek environment, Jalan Ahmad Yani No.16, South Cikampek Village, Cikampek District, Karawang Regency. The research used is quantitative descriptive research using a survey method with a questionnaire. The population in this study was 164 employees working within the RSIA Sentul Cikampek environment with the sample limited to employees with less than 1 year of service. The minimum number of samples taken was 30 respondents.